2019
DOI: 10.1016/j.ahj.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor antagonist pre-treatment and early post-treatment to minimize reperfusion injury after ST-elevation myocardial infarction: The MINIMIZE STEMI trial

Abstract: Background Mineralocorticoid receptor antagonist (MRA) therapy has been shown to prevent adverse left ventricular (LV) remodeling in ST-segment elevation myocardial infarction (STEMI) patients with heart failure. Whether initiating MRA therapy prior to primary percutaneous coronary intervention (PPCI) accrues additional benefit of reducing myocardial infarct size and preventing adverse LV remodeling is not known. We aimed to investigate whether MRA therapy initiated prior to reperfusion reduces my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Incorporating CMR’s precise myocardial biomarkers has accelerated the evaluation of a number of complementary therapeutic approaches. For instance, Bulluck and colleagues [ 192 ] evaluated treatment with a mineralocorticoid receptor antagonist drug intravenously at the time of primary percutaneous coronary intervention (PCI) and continued orally for 10 weeks after PCI; CMR was performed in the first week and again after 3 months. While mineralocorticoid receptor antagonist therapy did not reduce infarct size, LV remodeling did improve.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Incorporating CMR’s precise myocardial biomarkers has accelerated the evaluation of a number of complementary therapeutic approaches. For instance, Bulluck and colleagues [ 192 ] evaluated treatment with a mineralocorticoid receptor antagonist drug intravenously at the time of primary percutaneous coronary intervention (PCI) and continued orally for 10 weeks after PCI; CMR was performed in the first week and again after 3 months. While mineralocorticoid receptor antagonist therapy did not reduce infarct size, LV remodeling did improve.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…At present, treatment strategies for preventing left ventricular remodeling after myocardial infarction are still limited. Therefore, it is very necessary to conduct in-depth research on the pathological mechanism of myocardial injury and ventricular remodeling after myocardial infarction, and to determine additional treatment targets and treatment schemes to prevent the adverse effects of left ventricular remodeling after myocardial infarction [6].…”
Section: Introductionmentioning
confidence: 99%
“…The current TOPCAT (Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist Trial, NCT00094302) [33], ALBATROSS [13], and MINIMIZE STEMI [14] trials have shown little cardiovascular bene t from MRA therapy, raising the question of whether MRA treatment is bene cial for cardiovascular diseases. This meta analysis suggests that MRA treatment reverses cardiac remodeling and improves diastolic and systolic function and clinical prognosis in post-AMI patients.…”
Section: Disscussionmentioning
confidence: 99%
“…However, in 2016, the ALBATROSS trial [13] (Aldosterone Lethal effects Blockade in Acute myocardial infarction Treated with or without Reperfusion to improve Outcome and Survival at Six months follow-up, NCT01176968) failed to show cardiovascular bene ts of MRA in patients admitted for AMI. Then, the current MINIMIZE STEMI trial [14] (Mineralocorticoid receptor antagonist pretreatment to MINIMISE reperfusion injury after ST-elevation myocardial infarction, NCT01882179) showed less adverse left ventricular remodeling in STEMI patients treated with MRA. The bene ts of MRA therapy for AMI patients remain controversial, and it is unclear whether AMI subtypes, treatment initiation time and duration, or left ventricular ejection fraction (LVEF) values affect MRA to improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 98%